Analisis Efisiensi Ruang Kantor pada Bagian Tata Usaha di SMK Kristen 1 Surakarta - Pingkan Debra Martamevia; Hery Sawiji; Jumiyanto Widodo (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This study aims to: (1) analyze the efficiency of office layout in the Administration department at SMK Kristen 1 Surakarta, (2) identify obstacles that hinder the achievement of office space efficiency, and (3) provide recommendations for rearrangement to improve the efficiency and productivity of employee work in the Administration office of SMK Kristen 1 Surakarta. This research used descriptive qualitative method with direct observation approach, interviews with related parties, and documentation data collection. The research subjects consisted of the head of administration, administrative staff, and several users of office facilities at SMK Kristen 1 Surakarta. The results showed that: (1) the office layout in the Administration department is not fully efficient, with many documents piled up on the work table, less than optimal work flow, and furniture placement that does not support productivity; (2) the obstacles faced include the less strategic placement of file cabinets and filing cabinets, inadequate air ventilation and lighting, and table arrangements that do not support effective workflow; (3) To overcome these obstacles, it is necessary to rearrange office furniture to better support accessibility, add storage facilities to reduce the accumulation of documents on employee desks, and increase ventilation and lighting to create a more comfortable work environment and support employee work efficiency.